2022
DOI: 10.1007/s13346-022-01251-1
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary drug delivery: an effective and convenient delivery route to combat COVID-19

Abstract: The recent outbreak of coronavirus disease 2019 (COVID-19) in Wuhan, China has spread rapidly around the world, leading to a widespread and urgent effort to develop and use comprehensive approaches in the treatment of COVID-19. While oral therapy is accepted as an effective and simple method, since the primary site of infection and disease progression of COVID-19 is mainly through the lungs, inhaled drug delivery directly to the lungs may be the most appropriate route of administration. To prevent or treat pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 87 publications
0
10
0
1
Order By: Relevance
“…Finally, the mode of EV administration is dependent on the disease’s severity, where IV is usually selected for direct and faster drug delivery into the bloodstream in severe COVID-19 cases. In contrast, oral route is often used in early COVID-19 patients when there is a need for effective and economical treatment that can be taken at home [ 114 , 115 ]. However, the route of administration is also dependent on the drug properties, and the patient’s individual circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the mode of EV administration is dependent on the disease’s severity, where IV is usually selected for direct and faster drug delivery into the bloodstream in severe COVID-19 cases. In contrast, oral route is often used in early COVID-19 patients when there is a need for effective and economical treatment that can be taken at home [ 114 , 115 ]. However, the route of administration is also dependent on the drug properties, and the patient’s individual circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In the realm of COPD management, the appropriate delivery of medications and the mitigation of potential side effects are pivotal considerations. Tailoring drug delivery methods to suit individual patient needs ensures optimal efficacy while minimizing adverse reactions [ 28 , 31 , 32 , 33 , 34 ]. By focusing on these essential aspects, healthcare providers can significantly enhance the lives of COPD patients, mitigating the impact of this challenging condition on the older population.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…Pulmonary inhalation is a promising treatment option for this disease owing to its efficacy and safety. It is believed that hydroxychloroquine (HCQ) and chloroquine (CQ) impede viral terminal glycosylation of ACE2; however, they do not alter ACE2 in mammalian cells; therefore, they might theoretically be used to treat neo-crown pneumonia [ 268 ]. Studies have shown that HCQ inhalation is safe and effectively tolerated [ 269 ].…”
Section: Application Of Pulmonary Drug Deliverymentioning
confidence: 99%